Sodium hypochlorite concentration sensor based on enhanced ionic volt effect and preparation method thereof
By constructing a copper nanowire sensor with integrated load gradient and double-sided load, combined with oxalic acid coating modification, the problem of low sensitivity for sodium hypochlorite concentration detection in the prior art is solved, and high sensitivity and low cost NaClO concentration detection is achieved.
Patent Information
- Application Number
- CN202411516442.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the sodium hypochlorite concentration detection method has low sensitivity and is difficult to meet the needs of low content detection, and the instrument analysis method is complex and costly.
Copper nanowires were synthesized by solvent thermal reduction method, and micro-oxidation was used to regulate the nanowire morphology, to construct a gradient of load, combined with the integrated design of double-sided loads, enhance the ion volt effect, and modify the oxalic acid coating to achieve High sensitivity detection.
It realizes high sensitivity detection of NaClO in a wide concentration range, with simple process and low cost, and is suitable for popular use in households.
Smart Images

Figure CN119395098A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular concentration sensors, and in particular relates to a sodium hypochlorite concentration sensor based on enhanced ionovoltaic effect and a preparation method thereof. Background Art
[0002] Sodium hypochlorite has multiple functions such as bleaching, sterilization, and disinfection, and can be widely used in papermaking, textiles, light industry, water purification, and public disinfection. It is well known that the use effect of sodium hypochlorite solution strongly depends on the effective chlorine concentration. However, due to factors such as evaporation, decomposition, and pollution, its concentration may decrease over time, or even fail, so that the expected effect cannot be achieved. Therefore, it is crucial to accurately and in real time detect the concentration of sodium hypochlorite. At present, the method for detecting the concentration of sodium hypochlorite mainly includes chemical analysis (colorimetric test paper method, iodine titration) and instrumental analysis (optical, electrochemical, and chromatography). Among them, the chemical analysis method has low sensitivity and is difficult to meet the low-content detection requirements. For instrumental analysis, although the concentration of sodium hypochlorite can be determined more accurately, the complex sample pretreatment and expensive equipment costs limit the general application.
[0003] In recent years, the ionovoltaic effect generated by the penetration of liquids in semiconductor nanochannels has attracted widespread attention. Specifically, based on the interaction of the solid-liquid interface, the difference in carrier concentration between the dry and wet regions can generate voltage and current signals associated with the ion concentration of the solution. Therefore, it is a smart solution to use the ionovoltaic nanogenerator for sodium hypochlorite concentration sensing. When the NaClO solution flows through the nanochannel, the change in its concentration will directly affect the distribution and migration of carriers. By monitoring the electrical signal, the specific selection and concentration detection of sodium hypochlorite can be achieved. In addition, thanks to the advantages of simple operation and high sensitivity, the new NaClO sensor can overcome the shortcomings of existing detection methods and provide a guarantee for the rapid, accurate and real-time detection of molecular concentrations. It is worth noting that it is critical to improve the power generation performance of the device, which is conducive to intuitive electrical signal changes, thereby broadening the linear detection range of the sensor. Summary of the invention
[0004] In order to solve the problems of low sensitivity of chemical analysis methods in the prior art and difficulty in meeting the requirements of low-content detection, the present invention provides a sodium hypochlorite concentration sensor based on enhanced ion voltaic effect and a preparation method thereof; the method firstly synthesizes copper nanowires by a solvent thermal reduction method, and then uses hydrogen peroxide to perform micro-oxidation to regulate the morphology of the nanowires; by constructing a gradient of the loading amount, the migration and concentration difference of the carriers are effectively increased; combined with a double-sided load integrated design, two thin film parallel circuits are equivalent, and the ion voltaic effect is effectively enhanced; after high-temperature calcination in an air atmosphere, the sensor is modified by an oxalic acid coating and combined with the interaction of specific functional groups, a high-sensitivity detection of NaClO in a wide concentration range (0.001-1wt%) is achieved.
[0005] The present invention is achieved through the following technical solutions:
[0006] A method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltaic effect, the specific steps are as follows:
[0007] The copper nanowires are dispersed in an alcohol solvent, and then heated after adding hydrogen peroxide solution. After a certain period of micro-oxidation, Cu / Cu x O nanowires, where x ranges from 1 to 2; the rectangular glass fiber is evenly divided into three regions, and the slightly oxidized Cu / Cu x O nanowires are tightly attached to the glass fiber, and the reverse side follows the same loading method, forming a sandwich-like structure with exactly the same upper and lower surfaces. Finally, it is calcined in an air atmosphere to obtain an asymmetric CuO water permeation power generation device. Oxalic acid solution is dipped with a brush and evenly coated on both sides of the asymmetric CuO water permeation power generation device to construct a specific activation layer, thereby completing the preparation of the NaClO sensor.
[0008] Furthermore, the preparation steps of the copper nanowires are as follows:
[0009] Dissolve copper salt and chloride salt in the reducing agent solution and continue stirring; then add the capping agent dropwise and stir to obtain a blue uniform solution; transfer the mixed solution to a microwave reactor and heat to react for a certain period of time. After the reaction, a deep red solution is obtained, which is washed with n-hexane and isopropanol and centrifuged at 3000 rpm. Repeat 3 times to collect copper nanowires.
[0010] Furthermore, the copper salt is at least one of anhydrous copper acetate, copper sulfate, copper nitrate, copper chloride, cuprous chloride or copper citrate; the chloride salt is at least one of ammonium chloride, sodium chloride, potassium chloride, tetrapropylammonium chloride or 1-hexyl-3-methylimidazolium chloride; the reducing agent is at least one of ethylene glycol, 1,2-propylene glycol, glycerol or polyethylene glycol; the capping agent is at least one of ethylenediamine, dodecylamine, N,N-dimethyltridecylamine, hexadecylamine, oleylamine or oleic acid.
[0011] Furthermore, the molar ratio of the copper salt to the chloride salt is 2:1-10:1; the molar ratio of the capping agent to the copper salt is 1:1-10:1; the microwave reaction temperature is 160-220°C, and the reaction time is 2-8h.
[0012] Furthermore, the alcohol solvent is at least one of methanol, ethanol, isopropanol or n-butanol.
[0013] Furthermore, the concentration of hydrogen peroxide is 5wt%-30wt%, the volume is 5-40ml; the micro-oxidation time is 6-18h, and the temperature is 20-60°C.
[0014] Furthermore, the mass increasing ratio is 1:2:3.
[0015] Furthermore, the calcination temperature in the air atmosphere is 300° C.-550° C., and the calcination time is 0.5-4 h.
[0016] Furthermore, the concentration of the oxalic acid solution is 0.1-5wt%, and the volume of the oxalic acid solution is 0.5-3ml.
[0017] Compared with the prior art, the advantages of the present invention are as follows:
[0018] The invention discloses a sodium hypochlorite concentration sensor based on enhanced ion voltaic effect and a preparation method thereof. By constructing a mass gradient of nanowires and combining a double-sided load integrated design, the ion voltaic effect is enhanced, and a high-performance CuO permeation nanogenerator with a sandwich structure is prepared to achieve efficient energy conversion. By means of specific coating modification, thanks to the redox reaction at the solid-liquid interface, efficient detection of NaClO concentration in a wide linear range is achieved. This device does not require an external power supply, and uses the electrical signal generated by the NaClO permeation process to complete NaClO concentration sensing. It has a simple process and low cost, making up for the defects of low detection limit and complex operation of the prior art, and is suitable for popular use in households. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following is a brief introduction to the drawings required for the specific embodiments or the prior art description. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, the elements or parts are not necessarily drawn according to the actual scale.
[0020] Figure 1 is a scanning electron microscope image of the copper oxide film described in Example 1;
[0021] Figure 2 is the short-circuit current generated when 30 μL of 1 wt%, 0.1 wt%, 0.01 wt%, 0.001 wt% NaClO solution and deionized water in Example 1 penetrate through the front end of the sensor;
[0022] Figure 3 is the linear fitting curve of the sensor in Example 1 for different NaClO concentrations;
[0023] Figure 4 This is a scanning electron microscope image of the nanowires after micro-oxidation with hydrogen peroxide described in Comparative Example 1;
[0024] Figure 5 It is the short-circuit current generated when 30 μL of 1 wt%, 0.1 wt%, 0.01 wt%, 0.001 wt% NaClO solution and deionized water in Comparative Example 4 penetrate through the front end of the sensor. DETAILED DESCRIPTION
[0025] In order to clearly and completely describe the technical solution and its specific working process of the present invention, the specific implementation methods of the present invention are as follows in conjunction with the accompanying drawings of the specification:
[0026] Example 1
[0027] This embodiment provides a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect and a preparation method thereof, comprising the following steps:
[0028] First, copper nanowires are prepared, which specifically includes the following steps:
[0029] Dissolve 6mmol of cuprous chloride and 1mmol of ammonium chloride in 100ml of ethylene glycol and stir for 40min. Then add 18mmol of oleylamine dropwise and stir for 2h to obtain a blue uniform solution. Transfer the mixture to a microwave reactor and react at 160℃ for 4h to obtain a deep red solution. After cooling to room temperature, wash with n-hexane and isopropanol and centrifuge at 3000rpm, repeat 3 times, and collect copper nanowires;
[0030] Then, 200 mg of copper nanowires were dispersed in 20 ml of isopropanol solvent, 10 ml of H2O2 solution was slowly added, and the Cu / Cu nanowires were obtained after micro-oxidation at 30 °C for 10 h. x O nanowires. Using the filtration technology, 1.5×6cm 2 The glass fiber is evenly divided into three areas, and the slightly oxidized Cu / Cu x O nanowires are tightly attached to the glass fiber, and the reverse side strictly follows the same loading method. Finally, it is placed in a tube furnace and calcined at 350°C in an air atmosphere to obtain an asymmetric CuO water permeation power generation device. Use a brush to dip 2ml of 0.1wt% oxalic acid solution and evenly apply it on both sides of the asymmetric CuO water permeation power generation device to construct a specific activation layer, thereby completing the preparation of the NaClO sensor.
[0031] 30 μL of NaClO solution with different mass fractions (0.001-1 wt%) was added dropwise to the end with less loading, and the generated I sc .like Figure 1 As shown in the figure, copper oxide nanowires are intertwined to form a three-dimensional network structure. Figure 2 and Figure 3 As shown, the generated current is between 10μA-51μA, and the NaClO solution shows a significant linear relationship with the electrical signal intensity. This is because the uneven distribution of mass causes the film thickness (i.e., the number of nanochannels) under the same area to change, thereby effectively reducing the internal resistance and increasing the current. More importantly, the gradient of the CuO loading mass at both ends of the film maximizes the difference in carrier concentration between the dry and wet regions, enhancing the electrical signal. Thanks to the enhanced ion voltaic effect, the sensor is able to efficiently detect NaClO concentrations over a wide range.
[0032] Example 2
[0033] This embodiment provides a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect and a preparation method thereof, comprising the following steps:
[0034] First, copper nanowires are prepared, which specifically includes the following steps:
[0035] Dissolve 3mmol of cuprous chloride, 3mmol of cupric chloride and 2mmol of potassium chloride in 100ml of ethylene glycol and stir for 1h. Then add 12mmol of hexadecylamine dropwise and stir for 2h to obtain a blue uniform solution. Transfer the mixture to a microwave reactor and react at 180℃ for 6h to obtain a deep red solution. After cooling to room temperature, wash with n-hexane and isopropanol and centrifuge at 3000rpm. Repeat 3 times to obtain copper nanowires.
[0036] Then, 200 mg of copper nanowires were dispersed in 40 ml of ethanol solvent, and 20 ml of H2O2 solution was slowly added dropwise. After micro-oxidation at 40 °C for 8 h, Cu / Cu x O nanowires. Using the filtration technology, 1.5×6cm 2 The glass fiber is evenly divided into three areas, and the slightly oxidized Cu / Cu x O nanowires are tightly attached to the glass fiber, and the reverse side strictly follows the same loading method. Finally, it is placed in a tube furnace and calcined at 450°C in an air atmosphere to obtain an asymmetric CuO water permeation power generation device. Use a brush to dip 1ml of 1wt% oxalic acid solution and evenly apply it on both sides of the asymmetric CuO water permeation power generation device to construct a specific activation layer, thereby completing the preparation of the NaClO sensor.
[0037] 30 μL of NaClO solution with different mass fractions (0.001-1 wt%) was added dropwise to the end with less loading, and the generated I sc The generated current is between 10 μA and 26 μA, and when the effective chlorine is less than 0.01 wt%, there is no obvious linear dependence between its concentration and the electrical signal intensity.
[0038] Example 3
[0039] This embodiment provides a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect and a preparation method thereof, comprising the following steps:
[0040] First, copper nanowires are prepared, which specifically includes the following steps:
[0041] 8mmol copper sulfate and 2mmol potassium chloride were dissolved in 100ml of a mixed solvent of ethylene glycol and polyethylene glycol and stirred for 1h. Then 8mmol hexadecylamine was added dropwise and stirred for 2h to obtain a blue uniform solution. The mixture was transferred to a microwave reactor and reacted at 200℃ for 4h to obtain a deep red solution. After cooling to room temperature, the mixture was washed with n-hexane and isopropanol and centrifuged at 3000rpm for 3 times to obtain copper nanowires.
[0042] Then, 200 mg of copper nanowires were dispersed in 40 ml of methanol solvent, 15 ml of H2O2 solution was slowly added, and the Cu / Cu nanowires were obtained after micro-oxidation at 60 °C for 10 h. x O nanowires. Using the filtration technology, 1.5×6cm 2 The glass fiber is evenly divided into three areas, and the slightly oxidized Cu / Cu xO nanowires are tightly attached to the glass fiber, and the reverse side strictly follows the same loading method. Finally, it is placed in a tubular furnace and calcined at 400°C in an air atmosphere to obtain an asymmetric CuO water permeation power generation device. Use a brush to dip 1ml of 2wt% oxalic acid solution and evenly apply it on both sides of the asymmetric CuO water permeation power generation device to construct a specific activation layer, thereby completing the preparation of the NaClO sensor.
[0043] 30 μL of NaClO solution with different mass fractions (0.001-1 wt%) was added dropwise to the end with less loading, and the generated I sc The generated current is between 7 μA and 25 μA, and when the effective chlorine is less than 0.01 wt%, there is no obvious linear dependence between its concentration and the electrical signal intensity.
[0044] Comparative Example 1
[0045] This embodiment provides a preparation method of a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect, which is basically the same as that in Example 1, except that: the H2O2 micro-oxidation time is 24h; 30μL of NaClO solution with different mass fractions (0.001-1wt%) is added dropwise to the end with less load, and the generated I sc The generated current is between 4μA and 26μA, and when the effective chlorine is less than 0.1wt%, there is no obvious linear dependence between its concentration and the electrical signal intensity. Figure 4 As shown in the figure, the high concentration of peroxide ions in the micro-oxidation process caused the original copper nanowires to be oxidized seriously, making the nanowire structure loose. 2- The diffusion rate of the nanostructured film is accelerated, destroying the linear structure and causing the induced electrical signal to decrease. In addition, due to the rough surface, the internal resistance of the film is also increased, which is also the reason for the low electrical signal. The current threshold range is small, and it is impossible to identify NaClO concentrations of different orders of magnitude by the intensity of the electrical signal.
[0046] Comparative Example 2
[0047] This embodiment provides a method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect, which is basically the same as that in embodiment 1, except that: Cu / Cu x O nanowires were uniformly loaded on the glass fiber. 30 μL of NaClO solution with different mass fractions (0.001-1wt%) was added to one end, and the generated I sc. Ultimately, the generated current is between 2μA-20μA, and when the available chlorine is less than 0.1wt%, there is no obvious linear dependence between its concentration and the electrical signal intensity. The uniform distribution of nanowires means that the carrier concentration per unit area is the same. When the same volume of NaClO solution is added dropwise, the number of captured holes remains unchanged, but the difference in carrier concentration between dry and wet areas is much lower than the gradient distribution, so the induced electrical signal is weakened and the effect of identifying low-concentration NaClO solutions cannot be achieved.
[0048] Comparative Example 3
[0049] This embodiment provides a method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect, which is basically the same as that in embodiment 1, except that: slightly oxidized Cu / Cu x O nanowires were loaded on one side of the glass fiber. 30 μL of NaClO solution with different mass fractions (0.001-1 wt%) was added to one end, and the generated I sc . Ultimately, the generated current is between 0μA-2μA, and there is no obvious linear dependence between the NaClO concentration and the electrical signal intensity. This is because the CuO film and glass fiber have excellent water absorption. In the case of double-sided loading, when the liquid drips from the upper surface of the film, it can quickly and evenly penetrate to the bottom, achieving double-sided wetting. This unique "sandwich" structure not only significantly increases the contact area between the material and the solution, but also enables two originally independent single-sided devices to be activated at the same time, resulting in the same dry-wet boundary area and the same hole flow direction, functionally achieving the effect of two CuO films in parallel. In addition, the overall load has a significant effect on the internal resistance of the film. Single-sided load devices often have a large internal resistance due to their relatively insufficient load, which is also the main reason for their low electrical signal intensity, so the NaClO concentration cannot be detected.
[0050] Comparative Example 4
[0051] This embodiment provides a method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry, which is basically the same as that in Example 1, except that no modification of oxalic acid solution is performed. 30 μL of NaClO solution with different mass fractions (0.001-1wt%) is added dropwise to the end with less load, and the generated I sc .like Figure 5 As shown in the figure, the generated current is between 8μA and 26μA, and there is no obvious linear dependence between its concentration and the intensity of the electric signal. This is because the -COOH in the oxalic acid molecule can react with Cu 2+A chemical reaction occurs to generate a Cu-O bond, which effectively enhances the interaction between molecules. In addition, a stable hydrogen oxalate coating is formed on the surface of the CuO film, which can undergo a redox reaction with NaClO, which is the key to the sensor's efficient and specific identification of NaClO.
[0052] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0053] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0054] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect, characterized in that: The specific steps are as follows: The copper nanowires are dispersed in an alcohol solvent, and then heated after adding hydrogen peroxide solution. After a certain period of micro-oxidation, Cu / Cu x O nanowires, where x ranges from 1 to 2; the rectangular glass fiber is evenly divided into three regions, and the slightly oxidized Cu / Cu x O nanowires are tightly attached to the glass fiber, and the reverse side follows the same loading method, forming a sandwich-like structure with exactly the same upper and lower surfaces. Finally, it is calcined in an air atmosphere to obtain an asymmetric CuO water permeation power generation device. Oxalic acid solution is dipped with a brush and evenly coated on both sides of the asymmetric CuO water permeation power generation device to construct a specific activation layer, thereby completing the preparation of the NaClO sensor.
2. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect as claimed in claim 1, characterized in that: The preparation steps of the copper nanowires are as follows: Dissolve copper salt and chloride salt in the reducing agent solution and continue stirring; then add the capping agent dropwise and stir to obtain a blue uniform solution; transfer the mixed solution to a microwave reactor and heat to react for a certain period of time. After the reaction, a deep red solution is obtained, which is washed with n-hexane and isopropanol and centrifuged at 3000 rpm. Repeat 3 times to collect copper nanowires.
3. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect as claimed in claim 2, characterized in that: The copper salt is at least one of anhydrous copper acetate, copper sulfate, copper nitrate, copper chloride, cuprous chloride or copper citrate; the chloride salt is at least one of ammonium chloride, sodium chloride, potassium chloride, tetrapropylammonium chloride or 1-hexyl-3-methylimidazolium chloride; the reducing agent is at least one of ethylene glycol, 1,2-propylene glycol, glycerol or polyethylene glycol; the capping agent is at least one of ethylenediamine, dodecylamine, N,N-dimethyltridecylamine, hexadecylamine, oleylamine or oleic acid.
4. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect as claimed in claim 2, characterized in that: The molar ratio of the copper salt to the chloride salt is 2:1-10:1; the molar ratio of the capping agent to the copper salt is 1:1-10:1; the microwave reaction temperature is 160-220°C, and the reaction time is 2-8h.
5. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect according to claim 1, characterized in that: The alcohol solvent is at least one of methanol, ethanol, isopropanol or n-butanol.
6. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect according to claim 1, characterized in that: The concentration of hydrogen peroxide is 5wt%-30wt%, and the volume is 5-40ml; the micro-oxidation time is 6-18h, and the temperature is 20-60℃.
7. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect according to claim 1, characterized in that: The mass increasing ratio is 1:2:
3.
8. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect as claimed in claim 1, characterized in that: The calcination temperature in the air atmosphere is 300° C.-550° C., and the calcination time is 0.5-4 h.
9. The method for preparing a sodium hypochlorite concentration sensor based on enhanced ion voltammetry effect as claimed in claim 1, characterized in that: The concentration of the oxalic acid solution is 0.1-5wt%, and the volume of the oxalic acid solution is 0.5-3ml.
10. A sodium hypochlorite concentration sensor based on enhanced ion voltaic effect, characterized in that: The method is prepared by any one of claims 1 to 9.